Global Impact and Challenges of Unconventional Monetary Policies : Background Paper. (Policy Papers; Policy Paper, 2013)
This paper provides case studies of 13 of the largest non-UMP countries. The case studies begin with an overview of recent macro-economic developments as well as capital flow patterns during the crisis up to the first U.S. tapering announcement in May 2013. Country experiences with capital inflows are judged along five dimensions: (i) the size of capital inflows, (ii) policies used to manage inflows, (iii) external stability, measured by exchange rate overvaluation and current account deficits relative to fundamentals,2 (iv) asset price and credit market reactions, and (v) financial sector stability. Case studies mostly draw on published IMF Staff Reports for each country, as well as the 2013 Pilot External Stability Report (IMF 2013d).